Analisis Kepuasan Pengguna terhadap Aplikasi Mobile JKN Menggunakan Technology Acceptance Model (TAM) - Sihombing, Andre Saputra; Wahidin, Ahmad Jurnaidi (LPPM STT Terpadu Nurul Fikri, 2025)
The development of digital technology has driven significant transformation in healthcare services, including the utilization of the Mobile JKN application developed by BPJS Kesehatan. This application is designed to facilitate participants’ access to various services, such as bill checking, claim information, and healthcare facility registration. However, several issues related to ease of use and interface convenience persist, which may affect user satisfaction. This study aims to analyze user acceptance and satisfaction with Mobile JKN using the TAM, focusing on five variables. The research employed a quantitative method by distributing online questionnaires to 121 respondents. The collected data were analyzed using validity and reliability tests and descriptive statistics in SPSS. The results show that all instrument items are valid and reliable, with a Cronbach’s Alpha value of 0.918. The percentage achievement for each variable ranges from 79% to 82%, indicating that users have a positive perception of the Mobile JKN application. These findings confirm that the TAM model is relevant for assessing technology acceptance in digital health services and provide a foundation for BPJS Kesehatan to improve service quality in its application-based services.